Comparative analysis of the structure and content of curricula for translators in higher education institutions of Ukraine and France (Educational Dimension, 2020)
The article provides a comparative analysis of the features of the structure and content of curricula for translators in higher education institutions in Ukraine and France. Possible ways of using French experience in the process of training in translation in domestic practice have been identified, in particular, in the context of the possibility of adapting the existing curricula for translators in Ukraine, taking into account the positive experience of similar training in higher education institutions in France. Proposals for taking into account the positive experience of the educational process of French institutions of higher education specializing in the training of specialists in the field of translation have been developed.